A hands-on guide on obtaining research ethics approval. Issue 1030 (9th June 2011) - Hunter, David
Abstract : It is an uncontested truth that many medical students and practising clinicians dread having to get their research proposal through a research ethics committee. In this paper, the author, a long-standing member of a research ethics committee, offers a practical guide on applying for research ethics approval, detailing common mistakes and flaws in applications, and giving specific guidance on getting through what can seem a daunting process.